2002
DOI: 10.1002/ffj.1101
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition and antioxidant activity of essential oils from Algerian Origanum glandulosum Desf.

Abstract: The essential oils obtained from Origanum glandulosum Desf., collected in four different localities of the Sètif region (north-eastern Algeria), were analysed by GC-MS and assayed for their antioxidative effectiveness. The antioxidant capacity of the oils was measured by the modified thiobarbituric acid reactive species (TBARS) assay, using egg yolk as oxidizable substrate in presence of the radical inducer 2,2 0 -azobis-(2-amidinopropane) dihydrochloride (ABAP). The activity was compared with those of˛-tocoph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
35
1
7

Year Published

2003
2003
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(52 citation statements)
references
References 11 publications
9
35
1
7
Order By: Relevance
“…Derivatives of phenolic acids, flavonoids, tocopherols, rosmarinic acid, carvacrol, and thymol are the most significant of them (Peter 2000;Pizzale et al 2002;Ruberto et al 2002). According to phytochemical database (USDA 2003), the number of different antioxidants in this spice reaches up to 34.…”
Section: The Influence Of Gamma-irradiation On Antioxidant Ability Ofmentioning
confidence: 99%
“…Derivatives of phenolic acids, flavonoids, tocopherols, rosmarinic acid, carvacrol, and thymol are the most significant of them (Peter 2000;Pizzale et al 2002;Ruberto et al 2002). According to phytochemical database (USDA 2003), the number of different antioxidants in this spice reaches up to 34.…”
Section: The Influence Of Gamma-irradiation On Antioxidant Ability Ofmentioning
confidence: 99%
“…This activity may be attributed primarily to the high content of phenolic components of the essential oils. 37) The chemical composition of essential oil of Syrian oreganum indicates that the phenolic compounds (carvacrol, carvacrol methyl ether and thymol methyl ether) are relatively rich in the essential oil (Table 1). In fact, recently it has been reported these this compounds actually have antioxidant ability.…”
Section: )mentioning
confidence: 99%
“…According to Table 4, it is possible to observe that among the oleoresins studied, the one that presented the greatest oxidative stability was the oleoresin of oregano, followed by RUBERTO et al, 2002). In some studies, the extract of oregano (5%) has shown to be more effective than the propyl gallate, BHT, and BHA at 100 µg.g -1 (MARTÍNEZ-TOMÉ et al, 2001).…”
Section: Characterization Of Oleoresinsmentioning
confidence: 99%